Structures under shock and impact XV - Schleyer, Graham Klaus; Syngellakis, S. (WIT transactions on the built environment, 2019)
Discussing the increasing need to protect civilian infrastructure and industrial facilities against unintentional loads arising from accidental impact and explosion events as well as terrorist attack, this book contains papers presented at the 15th International Conference on Structures under Shock and Impact.